DESENTRALISASI, SISTEM PENGENDALIAN AKUNTANSI DAN KINERJA DINAS PADA PEMERINTAH KOTA PALANGKA RAYA - Wahyudin Noor (EKUITAS (Jurnal Ekonomi dan Keuangan), 2009)
This paper reports the results of a study which was conducted in government offices in Palangka Raya and investigated the relationships between (a) decentralization and the use of accounting control systems, (b) the use of accounting control systems and government office performance, and (c) the decentralization and government office performance. The performance was assessed using the heads of office perception of their office (unit's) performance. Samples taken in the research, were involved government offices in Palangka Raya. Analysis units utilized were the heads of offices, since they were mostly involved in budget processing in the offices. Data were collected through questionnaires, out of 112 questionnaires sent, only 66 questionnaires could be processed. The answers of the respondences are analyzed by using path analysis. The result showed that decentralization and accounting control system influence the performance. But empirically result shows that decentralization had no significant effect on performance. This study indicated that accounting control system was a mediator in the relationship between decentralization and performance